Resources in shaping the efficiency of dynamic capabilities of Polish enterprises - Sh. Tsifert; K. Kshakevich (Управление)
The dynamic capabilities, representing the organization’s competence to integrate, create and reconfigure internal and external competencies to ensure compliance with constantly changing environmental conditions, allow the organization to achieve a competitive advantage in the long term. The assumption of the background about the importance of dynamic capabilities for understanding the phenomenon of competition raises the question of the variables, affecting the effectiveness of the processes of formation of dynamic capabilities.The aim of this paper is discussion of the results of studies on the impact of resources on the effectiveness of the processes of formation of dynamic capabilities of Polish enterprises. The nature and essence of dynamic abilities of enterprises have been characterized in the article, the value of resources in the processes of formation of dynamic abilities of Polish enterprises has been noted, which subsequently allowed to formulate conclusions about the relationship between resources and efficiency of processes of formation of dynamic abilities of Polish enterprises have been formulated. The results of the research resources in the processes of formation of dynamic capabilities of Polish enterprises, presented in the paper, are fragment of the research project, whose goal is to develop a paradigm concept of dynamic capabilities from the perspective of strategic management, identification and analysis of dynamic capabilities of Polish enterprises.According to respondents in the process of questioning, sources of efficiency should be sought in external variables (customer loyalty, market share, sales growth), but not in internal variables (employment growth). Such a state, indicating the orientation of the organization outward, should be considered correct from the point of view of the logic of the dominant ways of constructing a strategy, since it indicates an understanding of the needs of the environment, while dynamically comparing with the expectations of this environment and the resources available to the organization.